Hubungan Motivasi Belajar dan Persepsi Siswa terhadap Matematika dengan Hasil Belajar Matematika Kelas X SMA Al Islam 1 Surakarta - Safira Rosyida; Wiwin Astuti (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study was conducted to analyze the relationship between students’ learning motivation and their perception of mathematics with mathematics achievement among tenth-grade students at SMA Al Islam 1 Surakarta. Mathematics was chosen as the focus because it is often considered a subject that presents significant challenges for students, both in terms of conceptual understanding and in shaping positive attitudes toward learning. The study employed a correlational quantitative method, with the population consisting of all tenth-grade students and the sample limited to class X-9, comprising 36 students. The instruments used were a motivation questionnaire, a perception questionnaire, and mathematics learning outcomes obtained from mid-semester test scores. Data analysis included normality testing and Pearson correlation to identify the relationship among variables. The results indicated that learning motivation did not have a significant correlation with mathematics achievement. In contrast, students’ perception of mathematics showed a significant correlation with their academic performance. These findings suggest that students’ positive perceptions of mathematics can play a crucial role in supporting better academic achievement, while motivation alone may not guarantee higher performance. This study contributes to a deeper understanding of the factors influencing mathematics learning outcomes and provides a foundation for further research to develop more comprehensive tools for measuring motivation. Future studies are also encouraged to consider additional variables such as teaching strategies, parental involvement, and the overall learning environment in order to present a broader analysis of student success.